Predicting the bending properties of Larix sibirica lumber using nondestructive-testing methods. (2nd July 2020) - Tumenjargal, Bayasaa; Ishiguri, Futoshi; Takahashi, Yusuke; Nezu, Ikumi; Baasan, Bayartsetseg; Chultem, Ganbaatar; Aiso-Sanada, Haruna; Ohshima, Jyunichi; Yokota, Shinso
ABSTRACT: This study aims to investigate whether it is possible to predict the modulus of elasticity (MOE) and modulus of rupture (MOR) of lumber produced from different heights using the stress-wave velocity of standing trees or the dynamic Young's modulus of logs in Siberian larch ( Larix sibirica ). A total of 190 pieces of lumber (38 by 89 mm in cross section) were cut from 111 logs obtained from 25 standing trees. Significant positive correlation coefficients were found between the stress-wave velocity of standing trees and MOE ( r  = 0.776) and MOR ( r  = 0.702) of this lumber. The dynamic Young's modulus of the logs also correlated significantly with MOE ( r  = 0.745) and MOR ( r  = 0.584) values. The results obtained in the present study suggest that stress-wave velocity and dynamic Young's modulus are useful for selecting superior trees in tree breeding and sorting logs for producing structural lumber.